Examining the effects of SERCA2a acetylation in the heart - Susser, Shanel (2016)
The sarcoplasmic reticulum Ca2+-ATPase (SERCA2a) is responsible for calcium transport in the heart and its dysfunction in heart disease and diabetes make it a target for treatment strategies. SERCA2a structure can be modified post-translationally by the addition of an acetyl protein via acetylation. Sirtuin3 (SIRT) is a deacetylase, which may interact with SERCA2a to reverse its acetylation. The aim of this study was to determine if SERCA2a function is altered by acetylation, if this occurs in the diabetic heart, and if SIRT3 influences SERCA2a acetylation. Our data indicates that modification to three SERCA2a acetylation sites impairs its activity in a cell culture model and that SERCA2a acetylation occurs at higher levels in the diabetic heart. Furthermore, SERCA2a is acetylated at higher levels in absence of SIRT3, suggesting that SIRT3 activity influences SERCA2a. Our data identifies possible therapeutic strategies to target and reduce SERCA2a acetylation in the diabetic heart. === February 2016